Use of protista and algae to study toxicity of dye compounds - Dias, Nicolina (2003)
Comparative assessment of the toxicological effects of two azo dyes [Reactive Orange 16 (R016); Congo Red (CR)] and two anthraquinone dyes [Remazol Brilliant Blue R (RBBR); Disperse Blue 3 (DB3)] was performed on two in vitro cell models, the ciliate protozoa Tetrahymena pyriformis and the microalga Selenastrum capricornutum. Growth impairment, viability assay using calcein AM and ethidium homodimer-1 (CAM/EthD-1 assay), grazing and morphometric assay were the tests performed on T pyriformis using 48 h-tests. They represented simple and fast bioassays providing overall information on the morphological and physiological state of the cells exposed to different dyes. The algal test measured growth inhibition after a 96-h exposure. The anthraquinone dye DB3 was found to be the most toxic dye among all the dyes tested. The EC50 value of 0.5 ± 0.0 mg/l detected in the algal test was 10 to 100-fold lower compared to other dyes tested.